Disasters Preparedness and Emergency Response: Prevention, Surveillance and Mitigation Planning - Goniewicz, Mariusz (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue welcomes research papers on new approaches that have been applied or are under development to improve preparedness and emergency response. We especially encourage the submission of inter-disciplinary and crosscutting research. We also encourage the submission of manuscripts that focus on various types of disasters, disaster and emergency research, and on policy or management solutions at multiple scales.